2017
DOI: 10.4025/actascibiolsci.v39i1.33400
|View full text |Cite
|
Sign up to set email alerts
|

<b>Shading effects on leaf life span and functional traits in the widespread species <i>Enterolobium contortisiliquum<i> (Vell.) Morong

Abstract: ABSTRACT. Enterolobium contortisiliquum occurs in native forests formations from southeast to northeast Brazil, and too in Argentina, Bolivia and Paraguay. The objective of this study was to evaluate shading effects in the early growth of E. contortisiliquum plants. We measured leaf gas exchange, chlorophyll content index, biomass allocation and leaf development in plants in sunny and shaded areas. The experiment was performed in Universidade Federal de Viçosa, campus Florestal, Minas Gerais, Brazil. To determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 34 publications
2
22
0
1
Order By: Relevance
“…On the other hand, Melo et al (2008) Seedling growth of tree species... found that for five levels of shading, the highest quality plants of Enterolobium contortisilliquum (Vell.) Morong developed both in full sun and under 20% shading; whereas, Souza et al (2017) found greater growth in seedlings of this species under full sun.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…On the other hand, Melo et al (2008) Seedling growth of tree species... found that for five levels of shading, the highest quality plants of Enterolobium contortisilliquum (Vell.) Morong developed both in full sun and under 20% shading; whereas, Souza et al (2017) found greater growth in seedlings of this species under full sun.…”
Section: Discussionmentioning
confidence: 59%
“…Enterolobium contortisilliquum (Vell.) Morong has more chlorophyll a and more total chlorophyll when grown in a shaded environment (Souza et al, 2017). Chlorophyll a absorbs light at wavelengths greater than 680 nm, while chlorophyll b absorbs light at shorter wavelengths (Rabinowitch and Govindjee, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Morong. (Fabaceae), is a leguminous species native to Brazil, and it is characterized as deciduous during winter and represents a pioneer and hygrophytic-selective species (Souza, Melo, Halfed, & Reis, 2017). This tree has been used in the restoration of degraded areas and mixed-species plantations because of its rapid growth, which can reach five meters in less than two years (Souza et al, 2017;Araujo & Paiva Sobrinho, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(Fabaceae), is a leguminous species native to Brazil, and it is characterized as deciduous during winter and represents a pioneer and hygrophytic-selective species (Souza, Melo, Halfed, & Reis, 2017). This tree has been used in the restoration of degraded areas and mixed-species plantations because of its rapid growth, which can reach five meters in less than two years (Souza et al, 2017;Araujo & Paiva Sobrinho, 2011). Nevertheless, this species presents low seedling germination because of an impermeable cover formed by macrosclereids and a high number of hydrophobic substances that induce the physical dormancy of the seeds (Baskin, Baskin, & Xiaojie, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Morong is considered a widespread species (Lima, Oliveira, & Rodrigues, 2009;Araújo & Paiva Sobrinho, 2011) and invasive with the potential to disrupt native plant communities (Cochrane, 1999). It occurs in native forest formations, in the Atlantic Forest domain (Lima et al, 2009;BFG, 2015) and in the Cerrado and Caatinga vegetation in northeastern Brazil (Souza, Melo, Halfeld, & Reis, 2017). At the southern limit of its distribution in Brazil, this species is found in seasonal forests, open fields, and shrub restinga habitat (Amorim, De Souza, Oliveira, Camacho, & De Melo, 2016).…”
Section: Introductionmentioning
confidence: 99%